2020
DOI: 10.1007/s11145-020-10096-4
|View full text |Cite
|
Sign up to set email alerts
|

Prosodic sensitivity and reading fluency of musicians and non-musicians

Abstract: This study investigates the effects of prosodic sensitivity on reading. Highly capable adult musicians (i.e., persons with potentially excellent prosodic skills) and non-musicians were compared in terms of prosodic sensitivity and reading. Furthermore, the study examines possible reciprocal effects of prosodic sensitivity and reading. Sixty native German-speaking university students, musicians (n = 30) and non-musicians (n = 30), completed three measures of prosodic sensitivity on the sentence level. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…For adults, Chan and Wade-Woolley (2018) found a regression coefficient of .20 for word-level PS on reading in English-speaking adults when controlling for receptive vocabulary, rapid automatized naming, phonological short-term memory and inhibitory control. Concerning sentence-level PS, Obergfell et al (2021) reported a regression coefficient of .25 on word-level reading in German-speaking adults when controlling for age and PA. The significant, direct contribution of PS on reading in the current study seems to be of moderate size, in line with previous studies.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…For adults, Chan and Wade-Woolley (2018) found a regression coefficient of .20 for word-level PS on reading in English-speaking adults when controlling for receptive vocabulary, rapid automatized naming, phonological short-term memory and inhibitory control. Concerning sentence-level PS, Obergfell et al (2021) reported a regression coefficient of .25 on word-level reading in German-speaking adults when controlling for age and PA. The significant, direct contribution of PS on reading in the current study seems to be of moderate size, in line with previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…PS describes the sensitivity to suprasegmental phonological processes such as stress, rhythm, timing and intonation in speech. Numerous studies with different orthographies and age groups have demonstrated that PS makes a unique contribution to word-level reading after controlling for PA and/or several reading-related precursors (English: Chan et al, 2020;Holliman et al, 2017a;2017b;Lin et al, 2018;Wade-Woolley, 2016;Spanish: Calet et al, 2015;Gutiérrez-Palma et al, 2016; English adults: Chan & Wade-Woolley, 2018; German adults: Obergfell et al, 2021). However, some studies did not find a unique effect of PS on word-level reading when controlling for PA (Wade-Woolley, 2016, for nonword reading) and morphological awareness (Deacon et al, 2018, for word reading) in English-speaking children.…”
Section: Empirical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…This means that neurobiological variation that affects auditory perception may also be associated with poor reading comprehension. Indeed, studies have found that rhythmic skill predicts reading skill in beginning readers (Tierney et al, 2021), that good musicians are also better at syntactic comprehension (Obergfell et al, 2021) and that priming with regular sequences of tones facilitates subsequent silent reading comprehension in children with developmental language disorders (Przybylski et al, 2013).…”
Section: Discussionmentioning
confidence: 99%